Post-organic/materic. body re-introduced to the body presented (2012)
This paper presents a review of the concept of the body incontemporary art from a current perspective based on thesemiotics of art. It also alludes to some Latin Americanartists, centering on Colombian artist Jose AlejandroRestrepo, who merges technological and political aspectsin works as original as with a strong critical content.